KNIGHT OF SHADOWS (BETWEEN YIN AND YANG): INTERPRETASI FILM CHINA DALAM PERSPEKTIF PSIKOLOGIS-FILOSOFIS - Ahmadi, Anas (Universitas Negeri Surabaya, 2018)
This study aims to explore the Knight of Shadows movie from a psychological-philosophical perspective in relation to yin and yang. The approach used in this study is psychological-philosophical about yin and yang. The research method uses a qualitative psychological-philosophical perspective. Data sources use dialogue in the Knight of Shadow movie. Sequential steps are used (1) identification, (2) classification, (3) reduction, (4) verification, (5) description of results and discussion of presentation, and (6). conclusion. The results of the study show that and films in the form of (1) world exchanges between humans and stealth, (2) stories of creatures of the earth (humans) and supernatural beings (stealth); (3) human death and clandestine in eternal places.